Surgical Wound Complications after Knee Cruciate Ligament Reconstruction in Patients with Atopic Dermatitis - Yokoe, Takuji; Tajima, Takuya; Yamaguchi, Nami; Morita, Yudai; Chosa, Etsuo (The Journal of Knee Surgery, 2020)
Atopic dermatitis (AD), sometimes referred to as eczema, is a common skin disease, and skin barrier dysfunction and immunological disorders are well recognized. However, surgical wound complications after orthopaedic surgery in patients with AD have not been described. This study aimed to report four patients with AD who developed foreign body reactions to FiberWire sutures with or without surgical wound infection (SSI) after knee cruciate ligament reconstruction (CLR). The mean age was 19.8 (range, 16–25) years, and patients 1 and 3 underwent reconstructions of the posterior and anterior cruciate ligament, respectively. At a mean of 7.5 (range, 4–10) weeks postoperatively, discharge from the surgical wound at the tibial side of the fixed graft was identified. All patients were treated with continuous saline lavage and antibiotics; however, their wounds did not heal. Second-look arthroscopy and hardware removal were performed at a mean 12.2 (range, 9–15) months postoperatively. Proliferated granulation tissue surrounding the FiberWire was identified. Intraoperative wound cultures were negative in three of the four patients. Histological examination of the tissues adjacent to the FiberWire revealed a foreign body reaction. All wounds healed immediately after the second surgery. In addition to SSI, foreign body reactions are more likely to occur in patients with AD than in those without AD. Preoperative management of AD by dermatologists and consideration of appropriate suture materials are mandatory to reduce surgical wound complications after knee CLR in patients with AD.
Keywords: knee cruciate ligament reconstruction; atopic dermatitis; foreign body reaction; surgical site infection